Nup42 and IP6 coordinate Gle1 stimulation of Dbp5/DDX19B for mRNA export in yeast and human cells. (16th October 2017) - Adams, Rebecca L.; Mason, Aaron C.; Glass, Laura; Aditi,; Wente, Susan R.
Abstract : The mRNA lifecycle is driven through spatiotemporal changes in the protein composition of mRNA particles (mRNPs) that are triggered by RNA‐dependent DEAD‐box protein (Dbp) ATPases. As mRNPs exit the nuclear pore complex (NPC) in Saccharomyces cerevisiae, this remodeling occurs through activation of Dbp5 by inositol hexakisphosphate (IP6 )‐bound Gle1. At the NPC, Gle1 also binds Nup42, but Nup42's molecular function is unclear. Here we employ the power of structure‐function analysis in S. cerevisiae and human (h) cells, and find that the high‐affinity Nup42‐Gle1 interaction is integral to Dbp5 (hDDX19B) activation and efficient mRNA export. The Nup42 carboxy‐terminal domain (CTD) binds Gle1/hGle1B at an interface distinct from the Gle1‐Dbp5/hDDX19B interaction site. A nup42‐CTD/gle1‐CTD/Dbp5 trimeric complex forms in the presence of IP6 . Deletion of NUP42 abrogates Gle1‐Dbp5 interaction, and disruption of the Nup42 or IP6 binding interfaces on Gle1/hGle1B leads to defective mRNA export in S. cerevisiae and human cells. In vitro, Nup42‐CTD and IP6 stimulate Gle1/hGle1B activation of Dbp5 and DDX19B recombinant proteins in similar, nonadditive manners, demonstrating complete functional conservation between humans and S. cerevisiae . Together, a highly conserved mechanism governs spatial coordination of mRNP remodeling during export. This has implications for understanding human disease mutations that perturb the Nup42‐hGle1B interaction. Abstract : Export of mRNA through nuclear pore complexes requires Mex67/Mtr2 export factors to bind both mRNA‐bound proteins (Nab2) and nucleoporins (Nups) with FG domains, followed by terminal removal of Mex67/Mtr2/Nab2 through activation of Dbp5 DEAD‐box ATPase by Gle1‐IP6 at the cytoplasmic face. Adams et al. demonstrate that Nup42 binds Gle1 at a distinct interface to enhance stimulation of Dbp5. Human mRNA export requires both Nup42‐hGle1B and IP6‐hGle1B interaction. This work reveals mechanisms for spatiotemporal coordination of Gle1‐Dbp5 activity with disease implications.